Mikrobiota Usus dan Osteoartritis - Redi Bintang Pratama; Khairun Nisa Berawi; Nurul Islamy (Penerbit Goodwood, 2021)
Osteoarthritis (OA) is one of the most commonly experienced musculoskeletal diseases. Various studies were conducted to find the relationship between the gut microbiota and the incidence of osteoarthritis. The gut microbiota encourages the production of proinflammatory cytokines and bacterial metabolites which are considered to be part of the pathophysiological mechanisms of osteoarthritis. Various risk factors that trigger osteoarthritis, such as age, gender, diet, and obesity have an influence on the gut microbiota. This suggests the possible involvement of the microbiota in the incidence of osteoarthritis. The increasing prevalence of osteoarthritis calls for an effective disease-modifying therapy strategy to relieve symptoms and slow the progression of the condition. The investigators hypothesized that modulation of the gut microbiota by external approaches might influence the progression of osteoarthritis. To date, some evidence suggests that gut microbiota intervention can be realized through probiotics, prebiotics, exercise, and fecal microbiota transplantation (FMT). Keywords: Osteoarthritis, Microbiota, Risk Factor